Spatial Patterns of Agriculture in Boyacá - Arias, Helmuth Yesid; Antosová, Gabriela (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article figures out spatial patterns for Boyacá’s agriculture and exposes the behavior of production. Applying gravitational concepts we describe relevant spatial interactions across municipalities usingvariables as population, output and linear distances. We perform an econometric model for detecting the class of spatial dependence showed by agricultural output as endogenous using as arguments distance toTunja and rural population. We deploy standard tools of spatial analysis and empirical strategies for identify clusters of towns according with their performance and productivity. Statistical contrast indicates that the most suitable scheme for describing spatial dependence in production is spatial lag model. Econometrics conveys important clues demonstrating that higher scales output is conducted to urban national markets and output produced with scarce scales is sold locally in local towns. A strong subjacent idea is that lagged municipalities are badly influenced by geographical isolation and high transportation costs do hinder the social and economic development in Boyacá.